Microzonation of Banja Luka for performance-based earthquake-resistant design. Issue 78 (November 2015) - Lee, V.W.; Manić, M.I.; Bulajić, B.Ð.; Herak, D.; Herak, M.; Trifunac, M.D.
Abstract: New microzonation maps for the city of Banja Luka in the Republic of Srpska in Bosnia and Herzegovina are presented based on the uniform-hazard-spectrum (UHS) methodology. The results are compared with the previous generation of microzonation maps published in the early 1970s, which were determined for the largest expected levels of shaking and for the spatial variations based on the soil site properties and the observed damage during the 1969 earthquake. The old and new methods are compared with emphasis on their role in the long-term criteria for regional earthquake-resistant design guidelines and the associated consequences. Highlights: Uniform Hazard Spectra (UHS) of strong earthquake ground motion. Geographic variations of seismic hazard in Banja Luka, Bosnia and Herzegovina. Seismic hazard model with distributed line sources and preferred azimuth. UHS method for performance based seismic design in urban environment.